2011
DOI: 10.1016/j.jhe.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A sight for sore eyes: Assessing the value of view and land use in the housing market

Abstract: We apply a hedonic model to the Geneva-Switzerland rental market to assess the value of view from dwellings and of land uses around buildings. Using a geographic information system, we calculate three-dimensional view variables, accessibility and land use variables. To our knowledge, this is the first paper to develop precise view measures at the dwelling level, considering surrounding land uses, in an urban context and with a large sample of 13,000 observations. The results show that view of various environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 25 publications
(19 reference statements)
4
36
1
5
Order By: Relevance
“…The higher is the quality of the landscape, the happier is the resident's life. This finding is very much consistent with previous studies, where the size of public green space in urban area was found to have a positive effect on the people's life satisfaction [45,51,78]. Models 2-4 are structured by adding several additional variables to the baseline Mode 1, including income, residence and individual social characteristics.…”
Section: Model Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The higher is the quality of the landscape, the happier is the resident's life. This finding is very much consistent with previous studies, where the size of public green space in urban area was found to have a positive effect on the people's life satisfaction [45,51,78]. Models 2-4 are structured by adding several additional variables to the baseline Mode 1, including income, residence and individual social characteristics.…”
Section: Model Resultssupporting
confidence: 88%
“…Without exception, all landscapes with enriched natural resources and beautiful environment attributes can considerably contribute to the nearby residential property values [48][49][50]. Furthermore, other researchers carried out similar studies to estimate economic value losses caused by different types of environmental damages, including but not limited to the value loss triggered by the existence of manufacturing facilities, cemetery, waste landfills, airport noise, and so on [51][52][53]. They demonstrated the fact that the discomfort landscape within the limit of sightseeing distance imposes negative effects on the housing prices.…”
Section: Valuing Landscape Using Conventional Techniquesmentioning
confidence: 99%
“…The land use in the downstream area also competes with settlement development. Housing areas in the flat plain close to the river offer amenities, such as a nice view of the water surface (Baranzini and Schaerer, 2011) and easy access to the river for recreation purposes. On the other hand, settlements near the river face greater flood risks and require expensive technical means of flood protection structures (e.g., flood dams) and specific asset protection, such as watertight doors and windows, protection walls, and backflow traps (FOWG, 2001).…”
Section: Land Use Trade-offs With Effects On Flood Protectionmentioning
confidence: 99%
“…Therefore, in the i th region, the AHI of the j th building can be estimated using Eq. (1). If the AHI of a building is higher than 1, it means that the value of the building is higher than the average of three nearby buildings.…”
Section: Data Collection Methodsmentioning
confidence: 99%